Pemikiran 'Ali Bin Abi Talib (R.A) Mengenai Konsep Syurga (Al-Jannah) dan Neraka (Al-Nar) - Wan Ali, Wan Zailan Kamaruddin (Jurnal Usuluddin, 2002)
Heaven (al-Jannah) and Hell (al-Nar) are two most popular concepts discussed and debated by Muslim scholars. Still, the problems arise from the disagreements among them. This article is an attempt to elaborate the view point of 'Ali bin Abi Talib (r.a) on the matter and its comparisons with the other Muslim sects and scholars.